Peculiarities of the investigation of frauds disguised as civil legal relations - K. D. Zaiats; D. D. Zaiats (Bulletin of Kharkiv National University of Internal Affairs)
The materials of judicial and investigative practice were analyzed, as a result of which shortcomings in the process of proof have been identified, to eliminate which it is appropriate to distinguish three stages in the fraud investigation methodology: 1) features of receiving and checking fraud reports and working with the victim; 2) collecting evidence of the use of deception or abuse of trust by a specific person before his or her detention; 3) collection of evidence after arrest and notification of suspicion to a person involved in committing fraud. It has been noted that each of the stages is characterized by a feature in relation to tactical tasks and means of solving them and is acceptable and understandable to employees of practical units, as it is related to specific procedural features of their work.